Bryophyllum pinnatum Compounds Inhibit Oxytocin-Induced Signaling Pathways in Human Myometrial Cells - Santos, Stefanie; Zurfluh, Leonie; Mennet, Mónica; Potterat, Olivier; von Mandach, Ursula; Hamburger, Matthias; Simões-Wüst, Ana Paula (Frontiers in Pharmacology, 2021)
Bryophyllum pinnatum has been used in the treatment of premature labor, first in anthroposophic hospitals and, recently, in conventional settings as an add-on medication. In vitro work with hTERT human myometrial cells showed that B. pinnatum leaf press juice inhibits the increase of intracellular free calcium concentration induced by oxytocin; a hormone known to play a role in labor. Our aim was to identify fractions/compounds in B. pinnatum press juice that contribute to this inhibitory effect, and to investigate their effect on oxytocin-driven activation of the MAPK cascade. Several fractions/compounds from B. pinnatum press juice led to a concentration-dependent decrease of oxytocin-induced increase of intracellular free calcium concentration, but none of them was as strong as B. pinnatum press juice. However, the combination of a bufadienolide and a flavonoid-enriched fraction was as effective as B. pinnatum press juice, and their combination had a synergistic effect. B. pinnatum press juice inhibited oxytocin-driven activation of MAPKs SAPK/JNK and ERK1/2, an effect also exerted by bufadienolide-enriched fraction. The effect of B. pinnatum press juice on oxytocin-induced signaling pathways was comparable to that of the oxytocin-receptor antagonist and tocolytic agent atosiban. Our findings further substantiate the use of B. pinnatum press juice preparations in the treatment of preterm labor.